Developing students’ professional and language competences through reading subject‑specific texts in English (the case of the Geography degree programme) - Mamatkulova, Fotima Ashirkulovna (The Lingua Spectrum, 2026)
This interdisciplinary study thoroughly investigates the essential pedagogical conditions, objective regularities, and innovative mechanisms of developing professional competence in geography students of higher education institutions through the systematic integration and reading of content-oriented (domain-specific) English scientific texts. The article provides a comprehensive, comparative-critical analysis of the specialized categorical apparatus, conceptual systems, and fundamental scientific sources, thereby determinating the crucial didactic role and absolute efficacy of the English for Specific Purposes (ESP) methodology in training future highly qualified geography specialists. Furthermore, within the structured process of systematic and integrated work with authentic geographical texts, the study explicitly outlines the deterministic criteria for significantly enhancing students’ proficiency in modern Geographic Information Systems (GIS) and global ecological-economic process terminology, their highly effective utilization of cognitive strategies in practice, and their advanced critical thinking capacity in objectively evaluating professional problems. Based on an integrative and synergetic approach, functional models for developing students’ independent research skills are proposed.